Al-Mg and U-Pb chronological records of Erg Chech 002 ungrouped achondrite meteorite. (15th February 2023) - Reger, Philip M.; Roebbert, Yvonne; Neumann, Wladimir; Gannoun, Abdelmouhcine; Regelous, Marcel; Schwarz, Winfried H.; Ludwig, Thomas; Trieloff, Mario; Weyer, Stefan; Bouvier, Audrey
Abstract: Achondrite meteorites are remnants of the earliest planetary differentiation processes in the Solar System. They have been used to anchor short-lived radiochronometers to absolute ages determined from long-lived radiochronometers. More specifically, when comparing the isotopic systematics of the short-lived 26 Al- 26 Mg chronometer anchored to absolute U-corrected Pb-Pb ages, inferences about the distribution of 26 Al (half-life of ∼717 000 yr) in the protoplanetary disk can be evaluated. The ungrouped achondrite Erg Chech (EC) 002 has a distinct mineralogy and more evolved elemental composition compared to basaltic achondrites. In situ and solution 26 Al- 26 Mg chronometry and 53 Mn- 53 Cr chronometry suggest that EC 002 formed within ∼0.7 to 2.2 Ma after the formation of Ca-Al-rich inclusions (CAIs), making it the oldest known sample of igneous crust in the Solar System (Barrat et al., 2021; Anand et al., 2022; Zhu et al., 2022; Fang et al., 2022 ). Here we present the U-corrected Pb-Pb age and 26 Al- 26 Mg age obtained by MC-ICPMS solution analysis of the same mineral separate samples of EC 002. In addition, six merrillite grains were analyzed by in-situ SIMS to determine their Pb-Pb individual ages. The U isotope composition of EC 002 exhibits internal heterogeneities between leached pyroxene ( 238 U/ 235 U = 137.766 ± 0.027) and the bulk rock ( 238 U/ 235 U = 137.8190 ± 0.0074). The Pb isotope composition of progressively leached pyroxenes are characterized by radiogenic 206 Pb/ 204 Pb ratios (ranging from 41 to 23487). Using the U isotope composition of the leached pyroxenes, the resulting age of the 207 Pb/ 206 Pb- 204 Pb/ 206 Pb isochron is 4565.87 ± 0.30 Ma (2σ). The weighted mean of the Pb-Pb ages of seven SIMS analyses of merrillites are 4564.3 ± 5.2 Ma (2σ). These similar ages (within uncertainty) indicate rapid cooling and the absence of significant thermal events after ∼4559 Ma on the parent body of EC 002. The 26 Al- 26 Mg isochron through a bulk rock, pyroxene, fine-grained and four plagioclase fractions defines an initial 26 Al/ 27 Al ratio of [8.89 ± 0.79] × 10 −6 corresponding to a formation age of 1.83 ± 0.12 Ma after CAIs ([5.23 ± 0.13] × 10 −5 ; Jacobsen et al., 2008 ). The initial 26 Al abundance is consistent with previous MC-ICP-MS 26 Al- 26 Mg reported systematics for EC 002 (Fang et al., 2022 ), but 0.46 ± 0.13 Myr older than the in situ SIMS 26 Al- 26 Mg age previously reported by Barrat et al. (2021) .When anchored to the absolute Pb-Pb age of CV3 CAIs (4567.30 ± 0.16 Ma; Connelly et al., 2012 ), the Al-Mg model age of EC 002 is 4565.47 ± 0.20 Ma, slightly younger than its U-corrected Pb-Pb age. The concordance of the Pb-Pb and 26 Al- 26 Mg ages of ungrouped CC achondrites when anchored to EC 002 suggest that 26 Al was homogeneously distributed between the NC and CC reservoirs at the time of their parent body accretion. Furthermore, the presence of internal U isotope heterogeneities found between mineral and whole-rock samples of EC 002 supports the need of U isotope analysis of meteoritic samples dated using the Pb-Pb chronometer.